Design, Synthesis, and Electrical Performance of Three-Dimensional Hydrogen-Bonded Imidazole-Octamolybdenum-Oxo Cluster Supramolecular Materials - Hongzhi Hu; Adila Abuduheni; Yujin Zhao; Yuhao Lin; Yang Liu; Zunqi Liu (Molecules)
Polyoxometalate (POM)-type supramolecular materials have unique structures and hold immense potential for development in the fields of biomedicine, information storage, and electrocatalysis. In this study, (NH4)3 [AlMo6O24H6]·7H2O was employed as a polyacid anion template, pentacyclic imidazole molecules served as organic ligands, and the moderate-temperature hydrothermal and natural evaporation methods were used in combination for the design and synthesis of two octamolybdenum-oxo cluster (homopolyacids containing molybdenum-oxygen structures as the main small-molecular structures)-based organic–inorganic hybrid compounds, [(C3N2H5)(C3N2H4)][(β-Mo8O26H2)]0.5 (1) and {Zn(C3N2H4)4}{[(γ-Mo8O26)(C3N2H4)2]0.5}·2H2O (2). Structural and property characterization revealed that both compounds crystallized in the P-1 space group with relatively stable three-dimensional structures under the action of hydrogen bonding. Upon temperature stimulation, the [Zn(C3N2H4)4]2+ cation and water molecules in 2 exhibited obvious oscillations, leading to significant dielectric anomalies at approximately 250 and 260 K when dielectric testing was conducted under heating conditions.